A systematic review of observational management of cutaneous basal cell carcinoma. Issue 7 (July 2022) - Goodall, R; Chicco, M; Wietek, N; Borsky, K; Harrison, C; Rodrigues, J
Summary: Background: Cutaneous basal cell carcinoma (BCC) is the commonest cancer in the United Kingdom and United States. Surgical excision is the most common treatment. This review summarises all published outcomes of observational/non-interventional management of cutaneous BCC. Methods: This PRISMA-compliant systematic review searched MEDLINE, EMBASE and CENTRAL databases from inception-June 2021. All studies reporting outcomes of observational management for BCC were included. Results: We identified 2529 titles, from which 4 full-text articles were eligible, reporting on 2298 individuals. Two studies were randomised controlled trials (RCTs) comparing histological clearance rates and adverse events following treatment with an inactive strategy (placebo cream) versus topical 5%-imiquimod (at different frequencies) for 6-12 weeks. Clearance rates ranged from 52-100% for imiquimod and 2-19% for placebo, with more adverse events associated with imiquimod. The other two studies used prospective cohort designs. One study assessed the natural history of BCCs managed expectantly in 39 individuals aged ≥80years. During the 15.8-month follow-up, 46.2% of lesions did not increase in size and 10.3% resolved. The remaining study compared treatment patterns of 1360 patients with non-melanoma skin cancer (NMSC) in individuals with or without limited life-expectancy (LLE). The LLE subgroup had a 5-year mortality rate of 43.3%, with no deaths attributed to NMSC. Only 3.3% of individuals with LLE underwent observational treatment. No study examined quality-of-life or cost-effectiveness. Conclusion: There has been limited investigation of observational management of BCC, despite possible advantages of this strategy. Future RCTs should compare quality-of-life outcomes and utility-adjusted survival following interventional or observational management of BCC.